Urban venezuela, a gaze from the barrios (2008)
Venezuela is the most urbanized country of Latin America. Venezuelan big cities, as most cities in Latin America, have a noticeable difference between the self constructed zones (without planning), called barrios in Venezuela, and the zones constructed according to the norms and other urban regulations, called urbanizations. In the article the helplessness in regulation terms of community life as well as in the planning practices stands out as well as the means and mechanisms that are adapted from foreign processes, mainly of European or North American societies. It seems that we do not dare to explore “the tropical asphalt jungle”. We are compelled to understand the situation in order to transform and to contribute to that knowledge. Teolinda Bolivar, co-author, chief of the Urbanization Department of Districts Equipment (1969-70), has battled during decades for the recognition of the barrios as parts of Venezuelan cities; a report of the journey to the recognition is displayed. Yves Pedrazzini, co-author, who has investigated - from inside- the violence and the urban chaos matters, contributes with interesting reflections on the subject.